Potential for yield and soil fertility improvement with integration of organics in nutrient management for finger millet under rainfed Alfisols of Southern India - Prabhakar, Mathyam; Gopinath, Kodigal A.; Sai Sravan, Uppu; Srasvan Kumar, Golla; Thirupathi, Merugu; Samba Siva, Gutti; Meghalakshmi, Guddad; Ravi Kumar, Nakka; Singh, Vinod Kumar (Frontiers in Nutrition, 2023)
Finger millet (Eluesine coracana L.) is gaining importance as a food crop with the increasing emphasis on nutritional aspects and drought resilience. However, the average productivity of the crop has stagnated at around 2000 kg ha-1 in India. Recently released nutrient responsive high yielding varieties are reported to respond better to application of fertilizers/manures. Further, substitution of chemical fertilizers with organic manures to maintain sustainable yields and improve soil health is gaining attention in recent years. Therefore, identifying the appropriate rate and source of nutrition is important to enhance the productivity of finger millet while improving the soil health. A field experiment was conducted during two rainy seasons (July-November, 2018 and 2019) to study the response of finger millet varieties to chemical fertilizers and farmyard manure (FYM) on growth, yields, N use efficiency, N uptake and on soil properties. Two varieties MR-1 and MR-6 were tested with four nutrient management practices viz., unamended control, 100% recommended dose of fertilizers (RDF; 40-20-20 kg NPK ha-1), 50% RDF + 50% recommended dose of nitrogen (RDN) as FYM and 100% RDN as FYM. Among the varieties, MR-6 outperformed MR-1 in terms of growth, yield, N use efficiency and N uptake. The yield enhancement was up to 22.6% in MR-6 compared to MR-1 across the nutrient management practices. Substituting FYM completely or half of the fertilizer dose increased the growth and yield of finger millet compared to application of chemical fertilizers alone. Similarly, the average biomass yield, ears m-2, grain yield, total N uptake and N use efficiency in response to nutrient management practices followed the order of 100% RDN as FYM > 50% RDF + 50% RDN as FYM > 100% RDF. The soil organic carbon, available N, P, K and S improved by 25.0, 12.9, 5.7, 6.1 and 22.6%, respectively in the plots under higher rate of FYM application (8 Mg ha-1) compared to plots under chemical fertilizers alone. We conclude that substituting chemical fertilizers either completely or by up to 50% with organic manures supplies adequate amounts of nutrients, improves the yield of finger millet, economic returns and soil properties.